Evaluating the cost of poverty alleviation transfer programs: an illustration based on PROGRESA in Mexico - Coady, David; Perez, Raul; Vera-Ilamas, Hadid (International Food Policy Research Institute, 2005)
One of the common criticisms of poverty alleviation programs is that the high share of administrative (nontransfer) costs substantially reduces the programs’ impact on poverty. But very little empirical evidence exists on program costs. For example, a recent extensive international review of targeted poverty alleviation programs in developing countries could find data on costs for only 32 out of the 111 programs reviewed. Even then, the numbers available were not always comparable. In this paper, we present a detailed analysis of the cost structure of a program recently introduced in Mexico, called PROGRESA. Our analysis shows how cost data can be used as the basis for an evaluation of the cost efficiency of anti-poverty programs. It cautions, however, that one must be very careful when interpreting cost numbers or undertaking comparisons across programs in order to avoid misleading conclusions. Any credible analysis of a program’s cost efficiency must involve a detailed analysis of cost structure and not simply provide aggregate cost information. We also highlight the importance of not neglecting private costs incurred by households in taking up transfers.